Quantum Hall effect in p-Ge/Ge₁₋xSix heterostructures with low hole mobility - Arapov, Yu.G.; Harus, G.I.; Karskanov, I.V.; Neverov, V.N.; Shelushinina, N.G.; Yakunin, M.V. (Физика низких температур, 2007)
The apparent insulator—quantum Hall—insulator (I—QH—I) transition for filling factor 1
has been investigated in p-type Ge/Ge₁₋xSix heterostructures with εFτ/h ≈ 1. Scaling analysis is
carried out for both the low- and high-field transition point. In low magnetic fields ωcτ < 1 pronounced
QH-like peculiarities for ν = 1 are also observed in both the longitudinal and Hall
resistivities. Such behavior may be evidence of a localization effect in the mixing region of Landau
levels and is inherent for two-dimensional structures in a vicinity of the metal—insulator transition.